Implementasi permainan tradisional engkek-engkek (engklek) sebagai sarana pengembangan keterampilan sosial peserta didik di sekolah dasar - Haliza, Muna Nur; Chumdari, Chumdari (Didaktika Dwija Indria, 2026)
This study aims to analyze the implementation of the traditional game of engkek-engkek (engklek) in developing the social skills of elementary school students. This study was conducted at CLC Prolific, Sabah, Malaysia. The research method used was a qualitative case study approach. Data collection techniques used were questionnaires, observation, and interviews. The results showed that the traditional game of engkek-engkek (engklek) can help develop students' social skills because it contains many social skill values. The results showed that the social skills of third-grade students through the implementation of the traditional game of engkek-engkek (engklek) were categorized as "Good" with a total average score of 75.98%. The highest social skill aspect was cooperation with an average percentage of 93.91%. The lowest social skill aspect was self-control with an average percentage of 57.76%. The conclusion of this study is that the implementation of the traditional game of engkek-engkek (engklek) can develop the social skills of elementary school students.